[Killer Whale Performance at Seven Seas Marine Life Park, 5] (1965)
Photograph of a killer whale performance at the Killer Whale Stadium, Seven Seas Marine Life Park in Arlington, Texas. Newtka, the killer whale, can be seen in the aquatic pool, opening her mouth for one of the trainers as he looks inside. Another trainer is standing on a platform within the stadium nearby Orchin, the Seven Seas mascot. A castle-themed backdrop is present behind the platform.